Realizing the Right to Reparations for Girl Soldiers: A Child-Sensitive and Gendered Approach - Bewicke, Aurora E. (Columbia Journal of Gender and Law, 2014)
The 2012 guilty verdict issued by the International Criminal Court (ICC) in the Thomas Lubanga Dyilo case has brought significant attention to the issue of child soldiering. Yet, despite global attempts to criminalize child soldier recruitment, armed groups’ willingness to capitalize on children’s inherent vulnerabilities and the proliferation of small arms have resulted in the continued use of large numbers of both boys and girls in armed conflict today. These youths suffer physical injury and psychological trauma. After the fighting has finished, they face further challenges reintegrating into civilian life. Girl soldiers in particular frequently experience reproductive health problems and gender-specific stigmatization. Yet, until recently, post-conflict justice mechanisms designed to address suffering and help populations transition have systematically failed to address the needs of both women and children, in particular the needs of girl soldiers. Even among programs initiated to reintegrate and rehabilitate child soldiers, very few have focused on girls, and some have even excluded them from the process. This Article will explore one of the main pillars of transitional justice, namely reparations, within this context. Specifically, it will address how to more effectively realize the right to reparations for girl soldiers. December 2011 witnessed the world’s first reparations judgment on the basis of unlawful child soldier recruitment, according to which Colombian paramilitary leader Fredy Rendón Herrera was sentenced and ordered to pay compensation for the illegal recruitment of minors, including girls. Following the March 2012 verdict in the Lubanga case—unless the conviction is overturned on appeal—we will now have the privilege to witness the ICC’s first judicial reparations procedures unfold, even if the implementation of these reparations remains some time away.